Direct-to-consumer advertising in Malaysia : skirting the regulations? - Zakaria, Syahiera Farhana; Othman, Noordin (IIUM Press, 2011)
Direct-to-consumer advertising (DTCA) of medicinal products is characterized by any statement or pictorial design targeted to general public that is meant to promote the use or supply of medical products or services ("A.MA Position Statement ", 2007). Generally, various forms of marketing techniques are used in DTCA including advertising in television, newspapers, pamphlets, radio and internet.